Leakage Current Waveforms and Arcing Characteristics of Epoxy Resin for Outdoor Insulators under Clean and Salt Fogs - Suwarno Suwarno; S. K. Ardianto (Institute for Research and Community Services, Institut Teknologi Bandung, 2008)
Ceramic outdoor insulators have been used in high voltage transmission lines since long time ago. Due to superiority in their resistance to pollution, recently, polymeric outdoor insulators are widely used. Epoxy resin is one polymer which shows good properties for outdoor insulation. During service, outdoor insulators may severe a certain degree of pollution which may reduce their surface resistance. Leakage current (LC) usually increase and degradation may take place. This paper reports experimental results on the leakage current waveforms and arcing characteristics of epoxy resin under clean and salt fog. The samples used are blocks of epoxy resin with dimension of 250 x 50 x 20 mm3 . The samples were put in a test chamber with dimension of 900x900x1200 mm3 with controllable humidity and pollution conditions. Clean and salt fog were generated according to IEC 60-1 and 507. The arcing experiment was done with incline plane test in accordance with IEC 587. AC voltage in the range from 5 kV to 50 kV with frequency of 50 Hz was applied. The LC waveforms up to flash over were measured. The magnitudes as well as harmonic content of the LC were analyzed. The correlation between LC waveforms and dry band arching phenomenon was elaborated. Visual observation of the arc on the sample surfaces was observed using a video camera. Experimental results indicated that LC magnitude on clean samples was slightly affected by humidity (RH). However, under salt fog, RH greatly affected the LC magnitude. The flashover voltage of clean samples under salt fog reduced significantly for fog conductivity of more than 1.2 mS/cm. Kaolin-polluted samples under salt fog showed an Ohmic behaviour. The LC magnitude was high and a large discrepancy of LC magnitude was observed for high applied voltage of larger than 25 kV. The largest LC magnitude was observed on salt-kaolin polluted samples under clean fog at high RH. LC waveforms analysis indicated that in general LC waveforms were distorted from sinusoidal. For clean samples under clean fog, THD of LC decreased with RH but slightly increased with the applied voltage. Large distortion at the peak of LC waveform was observed on kaolin polluted sample under salt fog of 3.6 mS/cm and high RH and high applied voltage. This correlates with corona arc on the sample surface. Similar behaviour was observed on kaolin-salt polluted samples under clean fog. Tracking arc experiment indicated that arc length LC magnitude and arc intensity increased with the pollutant conductivity. The THD also significantly increased with pollutant conductivity. At conductivity of less than 0.6 mS/cm the unsymmetrical LC waveforms were obtained. However, symmetrical LC waveforms were observed for conductivity of 0.9 and 1.2 mS/cm. The change of LC magnitude and waveform at different condition of samples may be useful for the diagnostics of insulator condition.